Estrabismo Acomodativo en Paciente de 5 años de edad. Presentación de caso. - Jara Pungil, Kevin Joel (2020)
Strabismus is a recurrent alteration present in children that, in addition to the aesthetic consequences, lead to a disorder in which the eyes do not look properly in the same direction, entailing important alterations in visual acuity and binocular vision. The main causes of a strabismus can be damage to the optic nerve or even a malfunction of the muscles that control the eye Your determination and due process are very important. The later its onset and the faster the treatment, the better the sensory prognosis, and vice versa. Strabismus, if not diagnosed and treated in a timely manner, can lead to amblyopia. Amblyopia can be translated as the decrease in visual acuity without justifying cause, recoverable with its necessary and timely treatment at an appropriate age.